Swimmers' training process control taking into consideration typology of bioenergetics - Moshkina, N.; Gibadullin, I.; Kuznetsova, Z. (Proceedings of the 7th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2019)
The research deals with the specific characteristics of swimmers` training management taking into account typologies of bioenergetics. For an effective and quick functional state and reserve capacities of athletes` organism diagnostics we held the test according to "D&K - TEST" express-diagnostics methodology created by Karlenko V.D. We created a block system of swimmers` sports training control. The block system includes the stages and the main components of management structure, where great attention is paid to information gathering concerning swimmers` functional training taking into account their typology of bioenergetics. We studied the ratio of swimmers` bioenergetics typology at the training stage according to the years of study. We estimated the level of functional state and swimmers` organism reserve capacities depending on their bioenergetics type. Specially selected training means and methods for swimmers were used in accordance with their typology of bioenergetics and it provided their physical readiness improvement, characterizing the effectiveness of competitive activity. We received the results of swimmers` functional state and reserve capacities of their organism, combined according to three types: aerobic, mixed and anaerobic.